2018
DOI: 10.1007/s00421-018-3900-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intensity and cardiorespiratory fitness on the acute response of arterial stiffness to exercise in older adults

Abstract: In older adults, PWV increases during seated rest and this response is attenuated after higher-intensity interval exercise, regardless of fitness level. This attenuation was also observed after moderate-intensity continuous exercise in adults with higher, but not lower fitness levels. Submaximal exercise reveals differences in the arterial stiffness responses between older adults with higher and lower cardiorespiratory fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 74 publications
2
19
0
Order By: Relevance
“…This finding is in line with previous studies in younger and older adults. 15,32 Despite a higher resting PWV in patients with AAA, exercise did not exacerbate aortic stiffness, with the changes in PWV during exercise recovery being similar between groups. The attenuation in aortic and systemic arterial stiffness after sub-maximal exercise, compared with seated rest, suggests there may be a reduction in aortic wall stress and an acute cardiovascular benefit from exercise for patients with AAA, similar to that reported for healthy adults.…”
Section: Aortic and Systemic Arterial Stiffness After Exercisementioning
confidence: 89%
See 2 more Smart Citations
“…This finding is in line with previous studies in younger and older adults. 15,32 Despite a higher resting PWV in patients with AAA, exercise did not exacerbate aortic stiffness, with the changes in PWV during exercise recovery being similar between groups. The attenuation in aortic and systemic arterial stiffness after sub-maximal exercise, compared with seated rest, suggests there may be a reduction in aortic wall stress and an acute cardiovascular benefit from exercise for patients with AAA, similar to that reported for healthy adults.…”
Section: Aortic and Systemic Arterial Stiffness After Exercisementioning
confidence: 89%
“…Cardiorespiratory fitness and AAA size were added as covariates. 15 Statistically significant interactions were further investigated with multiple comparisons using Fisher's least significant difference approach. 28 Analyses were conducted using SPSS (version 22; IBM, Armonk, NY, USA) and statistical significance was set at p .05.…”
Section: Pulse Wave Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, combined AER and RES chronic regimes have resulted in beneficial changes in resting wave reflection and/or arterial stiffness measures for older adults (Cook et al, 2006 ), women with metabolic syndrome (Eleuterio-Silva et al, 2013 ), obese men/women (Yang et al, 2011 ), patients with cardiovascular disease (Zhang et al, 2018 ) and hypertensive adults (Li et al, 2015 ; Jeon et al, 2018 ). The inclusion of AER following RES during an acute exercise session may counteract the potential negative effects of RES (Fahs et al, 2009 ; Sardeli et al, 2018 ; Tai et al, 2018 ) with acute AER reported to improve wave reflection and/or arterial stiffness measures in young (Munir et al, 2008 ; Lane et al, 2013 ; Milatz et al, 2015 ; Kobayashi et al, 2017 ) and older (Perissiou et al, 2018 ) healthy adults. Identifying both the acute and chronic responses of wave reflection and/or arterial stiffness in clinical populations could assist in establishing superior and safe exercise prescription for enhanced cardiovascular function and long-term health in these cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The drop of exmPAP and PAWP with higher performance may reflect better vascular compliance in patients with higher cardiorespiratory fitness (CRF, expressed by peak power). [37][38][39] A PVR threshold >3WU has been suggested at rest 17 and exercise 19 and was reached at 100W (3.8WU±1.5). Across all variables CRF turned out to play a major role in the definition of exPH.…”
Section: Discussionmentioning
confidence: 97%